Accounting for Goodwill - HUBER, STEFAN J.; MCCLURE, CHARLES G. (Journal of Accounting Research, 2025)
ABSTRACT A significant portion of a merger's purchase price is allocated to goodwill. Currently, goodwill is not amortized but rather tested annually for impairment. When managers of acquiring firms care about earnings, goodwill's accounting treatment can have large effects on future earnings and may influence how much a manager will bid for a target company. We quantify the effects of goodwill accounting by estimating a structural model of corporate takeovers. Our estimates suggest accrual accounting increases buyout premia by an average of approximately 11 percentage points. If firms needed to amortize goodwill over 10 years, we estimate premia would reduce by 4.9 percentage points and M&A volume would shrink by 4.1% or $67 billion per year. Furthermore, the fraction of private equity acquirers would increase by 6.9 percentage points, shifting control over productive assets to the private and financial sector. Our results suggest the accounting treatment for goodwill has a meaningful effect on the market for corporate control.